History Of Bukhara Literary Environment In Sources (Texas Journal of Philology, Culture and History, 2024)
This article presents the sources of studying the history of the literary environment of Bukhara in the 20th century. Names and authors of sources are cited and analyzed. The source studies of the period were studied in several stages. Works created in the first quarter of the 20th century during the Bukhara Emirate and the Bukhara People's Soviet Republic. Sadriddin Aini, Muhammad Ali Baljuvani, Haji Muhammad Nematullah Muhtaram, Afzal Makhdum Pirmasti Bukhari, Haji Azim Sha'ri, Mir Muhammad Siddiq Hashmat Bukhari, Sharifjan Makhdum Sadr Zia, Mirza Salimbek, Muhammad Sadiqkhoja Gulshani were published in different years. The works of Tughrali Ahrari, Mirza Hayit Sahbo, Sayyid Mansur Olimi, Sayyid Muhammad Nasir ibn Muzaffar, Akkos Bukhari, Mirza Sirojiddin Hakim, Abdullahhoja Abdi, Mirza Abdulazim Sami, Qari Rahmatullah Vozeh can be mentioned